Heterologous production of family 5 fungal endo-1,4-B-mannanases in Saccharomyces cerevisiae - Setati, Mathabatha Evodia (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2002.